Effect of feeding fermented palm kernel cake on performance of broiler chickens - Alshelmani, Mohamed Idris; Loh, Teck Chwen; Foo, Hooi Ling; Sazili, Awis Qurni; Lau, Wei Hong (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2013)
A total of 245 Cobb 500 one-day old chicks were raised in open house system at the poultry unit, Universiti Putra Malaysia. The birds were randomly distributed on 7 dietary treatments with 5 replicates per treatment. The chicks were fed 0, 5, 10, 15% palm kernel cake (PKC), and 5, 10, 15% fermented palm kernel cake (FPKC). The birds were fed ad libitum, and the trial lasted for 42 days. The objective of the experiment was to determine the effect of feeding FPKC on broiler performance. The results obtained showed that body weight (BW) and body weight gain (BWG) were significantly (P<0.05) decreased for broilers fed diet with 10% and 15% PKC compared to those groups fed diet with 0% PKC, whereas feed intake (FI) and feed conversion ratio (FCR) were not significantly (P>0.05 different. No significant effect in BW and BWG for broilers fed 5% PKC or 5, 10, 15% FPKC. The birds fed 10 and 15% FPKC produced significantly (P<0.05) higher BW and BWG compared to those groups fed 10 and 15% PKC, respectively. The study showed that FPKC can be included up to 15% to broiler diets without any adverse effect.